Identity Politics: a Study of the Historicity Politics Identity of the Hadrami Community in Indonesia - Bagus Prayogi; M. Khoirul Hadi Al-Asyari (Islah: Journal of Islamic Literature and History, 2021)
The community of Arab descent in Indonesia is a marginalized or minority community. In addition, they are also the least studied community in Indonesia. Many non-Arabs do not know that most of the Arabs in Indonesia are Hadrami people who come from Yemen and not from the original Arabs or Hejaz. Most Indonesians are also unaware of the significant social and cultural differences between countries in the Middle East region, particularly with regard to the history of internal relations within the Hadrami community in Indonesia. The Hadrami people come to Indonesia with several motivations, namely getting a better life, getting away from criminal and civil problems, the existence of conflicts and wars in their place of origin and so on. Different backgrounds in terms of culture and social become a problem. These cultural and social differences make it difficult for them to adapt and acculturate to indigenous peoples. Even so, they are still looking for a balance point in order to become part of the indigenous community. For example, they marry native women and men. This accommodation process is experienced by many other diaspora communities, which is always accompanied by pressure due to the increasing number of mixed-breed populations in their communities. In the book entitled, Seeking Identity, the internal relations between Arabs as immigrant communities and their external relations with the wider community are explained, including the top level authorities, namely the government, during the Dutch East Indies, the Japanese occupation and the Republic of Indonesia. This article deals with the history of identity by using research materials which are dominated by library materials. The title raised is Identity Politics: Historical Studies of the Identity Politics of the Hadrami Society in Indonesia. There are three questions in this article. First, what is the identity and identity politics of the Hadrami people in Indonesia. Second, what is the history of the Hadrami people in Indonesia. Third, what is the history of the Hadrami community's identity politics in Indonesia. This paper uses an analytical context approach to explain the concept of identity and identity politics. In addition, the purpose of this article, namely: 1). knowing the identity and identity politics of the Hadrami community in Indonesia; 2). knowing the history of the identity politics of the Hadrami people in Indonesia; and 3). knowing the identity politics of the Hadrami people in Indonesia.